Lithium Difluorophosphate as an Effective Additive for Improving the Initial Coulombic Efficiency of a Silicon Anode. Issue 18 (4th August 2020) - Li, Chao; Zhu, Weicheng; Lao, Banggui; Huang, Xiangxuan; Yin, Huibin; Yang, Zhenyu; Wang, Hongyu; Chen, Deliang; Xu, Yongjun
Abstract: Silicon anodes usually endure low initial coulombic efficiency (ICE) in applications for lithium‐ion batteries (LIBs), although the volume expansion and structural stability has been greatly improved under many efforts in the recent years. During the first charge and discharge, a large number of lithium ions can participate in the formation of a solid electrolyte interface (SEI) on anode surface, such as LiF, Li2 CO3 and many Li‐based compounds, resulting in low efficiency, particularly as the nano‐sized silicon is widely applied to solve the volume effect. Herein, we find that the lithium difluorophosphate (LiPO2 F2, LiDFP) additive shows some special properties, which greatly improve the reversible capacity in the first discharge. The silicon nanoparticles can deliver an ICE of 70.6 % with 2 wt% LiDFP in the electrolyte, which is increased by 17.7 % compared with the cell without LiDFP (ca. 52.9 %). By comparing the XPS and NMR results, it appears the LiDFP may reduce the number of lithium ions involved in the SEI reaction in the electrolyte during the first discharge, and thus the ICE can be improved. Abstract : Adding up : Lithium difluorophosphate (LiPO2 F2, LiDFP) additive leads to greatly improved reversible capacity in the first discharge. The silicon nanoparticles can deliver an initial coulombic efficiency (ICE) of 70.6 % with 2 wt% LiDFP in the electrolyte, which is an increase of 17.7 % compared with the cell without LiDFP (ca. 52.9 %). LiDFP may reduce the number of lithium ions involved in the solid electrolyte interphase reaction in the electrolyte during the first discharge, and thus lead to improvements in the ICE.